Preface - Seidl, Martina; Clarke, Peter (Electronic Communications of the EASST, 2011)
Collocated with the ACM/IEEE International Conference on Model-Driven Engineering Languages and Systems (MODELS), the Educators’ Symposium (EduSymp) focuses on the huge topic of software modeling education ranging from experience reports and case studies to novel pedagogical approaches. In the following, we shortly report on the 6th EduSymp held in October 2010 in Oslo.